Combination of searches for invisible higgs boson decays with the ATLAS Experiment - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Dreyer, Sascha S.; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; et al. (Physical review letters, 2019)
Dark matter particles, if sufficiently light, may be produced in decays of the Higgs boson. This Letter presents a statistical combination of searches for H→invisible decays where H is produced according to the Standard Model via vector boson fusion, Z(ℓℓ)H, and W/Z(had)H, all performed with the ATLAS detector using 36.1 fb−1 of pp collisions at a center-of-mass energy of s√=13 TeV at the LHC. In combination with the results at s√=7 and 8 TeV, an exclusion limit on the H→invisible branching ratio of 0.26(0.17+0.07−0.05) at 95% confidence level is observed (expected).